If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3a + -7)(5w + -8) = 0 Reorder the terms: (-7 + 3a)(5w + -8) = 0 Reorder the terms: (-7 + 3a)(-8 + 5w) = 0 Multiply (-7 + 3a) * (-8 + 5w) (-7(-8 + 5w) + 3a * (-8 + 5w)) = 0 ((-8 * -7 + 5w * -7) + 3a * (-8 + 5w)) = 0 ((56 + -35w) + 3a * (-8 + 5w)) = 0 (56 + -35w + (-8 * 3a + 5w * 3a)) = 0 (56 + -35w + (-24a + 15aw)) = 0 Reorder the terms: (56 + -24a + 15aw + -35w) = 0 (56 + -24a + 15aw + -35w) = 0 Solving 56 + -24a + 15aw + -35w = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -24a + 15aw + -56 + -35w = 0 + -56 Reorder the terms: 56 + -56 + -24a + 15aw + -35w = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -24a + 15aw + -35w = 0 + -56 -24a + 15aw + -35w = 0 + -56 Combine like terms: 0 + -56 = -56 -24a + 15aw + -35w = -56 Add '35w' to each side of the equation. -24a + 15aw + -35w + 35w = -56 + 35w Combine like terms: -35w + 35w = 0 -24a + 15aw + 0 = -56 + 35w -24a + 15aw = -56 + 35w Reorder the terms: 56 + -24a + 15aw + -35w = -56 + 35w + 56 + -35w Reorder the terms: 56 + -24a + 15aw + -35w = -56 + 56 + 35w + -35w Combine like terms: -56 + 56 = 0 56 + -24a + 15aw + -35w = 0 + 35w + -35w 56 + -24a + 15aw + -35w = 35w + -35w Combine like terms: 35w + -35w = 0 56 + -24a + 15aw + -35w = 0 The solution to this equation could not be determined.
| 8/x=4/15 | | 9/4÷18/7 | | X*7/8 | | 0.19x+0.5(x-4)=0.01(2x-1) | | 18/x=12/28 | | 0.09Xx=105.53 | | -x^5=8 | | 4a+b=45 | | 4(5x-4)=104 | | 3a-6=-18 | | 32+x+43=180 | | 54x^2-87+35=0 | | (5-y)(3y+8)=0 | | 4a+b=27 | | 2.5x+3.75=15 | | 9ab-6a+5b-3= | | b+9+6b-9= | | 3x+11=-7+x | | 3sinx=-1.2 | | 22=7.34+b | | 2m-10+5m-80=180 | | 2(3s+6)=32 | | 4z+3-9x= | | 2k+9k= | | 8x+8=2x+3 | | y=2xy+6y-10 | | 16.95=1/x | | 5(4+2x)+2x=176 | | 3+2m-7=10 | | Y2=-1/4x | | 9x-(2x-10)=40 | | 0.5=8/x |